2012
DOI: 10.1021/nn303217q
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Luminescence Quenching of Colloidal Quantum Dots

Abstract: A high luminescence efficiency is an important property of colloidal quantum dots (QDs), and quantum yields higher than 90% have been reported for coreÀshell QDs. 1 High efficiencies are especially important for application of QDs as luminescent biolabels, 2 in QD lasers, 3 in spectral converters for warm white LEDs, 4,5 electroluminescent devices, 6 and solar concentrators. 7 Luminescence efficiencies are strongly temperature-dependent. 8 Extensive temperature-dependent luminescence studies for colloidal QDs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
298
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(318 citation statements)
references
References 44 publications
16
298
2
2
Order By: Relevance
“…42 To gain more insights, these temperature-dependent PL spectra were analyzed in details. As shown in figure S5 in the supporting information, the absence of defect related emission in the PL spectra of QDs at 5 K demonstrated that the surface defects states of resulting QDs are well-passivated.…”
Section: Resultsmentioning
confidence: 99%
“…42 To gain more insights, these temperature-dependent PL spectra were analyzed in details. As shown in figure S5 in the supporting information, the absence of defect related emission in the PL spectra of QDs at 5 K demonstrated that the surface defects states of resulting QDs are well-passivated.…”
Section: Resultsmentioning
confidence: 99%
“…We have used the experimental linewidth data of ascending temperature to extract the intraband relaxation time (τ in = 2ħ/FWHM) used in our simulation as described in the calculation of the spontaneous radiative rate from the excitonic bound states and continuum-states in section 2.2. This helps to model the linewidth of the simulated PL spectra according to the Lorentzian broadening lineshape [eqn (9)] for an accurate estimate. The extracted τ in is shown in Fig.…”
Section: Comparison Of Theoretical and Experimental Resultsmentioning
confidence: 99%
“…Brought to you by | MIT Libraries Authenticated Download Date | 5/13/18 8:01 AM It is a well known fact that the QD emission intensity weakens [25] when strong optical excitation is applied due to issues related to photostability or when the QDs are subjected to high temperatures due to thermal droop, which is the case for the QDs integrated on high-power LEDs. To address this problem, researchers from Samsung proposed the integration of QDs into silica monoliths [26].…”
Section: Color-converting Colloidal Materials For Lightingmentioning
confidence: 99%